2002
DOI: 10.1159/000066763
|View full text |Cite
|
Sign up to set email alerts
|

Esberitox<sup>®</sup> N as Supportive Therapy when Providing Standard Antibiotic Treatment in Subjects with a Severe Bacterial Infection (Acute Exacerbation of Chronic Bronchitis)

Abstract: 53 patients with planned antibiotic therapy for the treatment of acute exacerbation of chronic bronchitis as an example of a severe bacterial infection requiring antibiotics were included in a prospective, multicentre, double-blind, placebo-controlled study. The chronic bronchitis was staged by forced expiratory volume of the 1st second (FEV1) measured in the infection-free interval prior to the current episode and had to be between 35 and 75% for the predicted value. Patients were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Of these, 48 articles were obtained for detailed evaluation and 19 RCTs [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . Figure 1 provides a flowchart of all included and excluded trials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 48 articles were obtained for detailed evaluation and 19 RCTs [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . Figure 1 provides a flowchart of all included and excluded trials.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen RCTs [9,[12][13][14][15][16][17][18][19][20][21][22][23][24] met all inclusion criteria and were assessed. The main characteristics of these studies are summarised in table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A well-designed double-blind, placebo-controlled trial of 53 people tested its benefits in acute exacerbations of chronic bronchitis. [39] All participants in this trial received standard antibiotic therapy. The results showed that people receiving the herbal medication experienced more rapid improvements in lung function than those given placebo.…”
Section: Plant-based Therapies For Copdmentioning
confidence: 99%